2018
DOI: 10.2196/preprints.10731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Development of VegEze: Smartphone App to Increase Vegetable Consumption in Australian Adults (Preprint)

Abstract: Background

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Although there are limited studies investigating the impact of LDC interventions on TDF domains of knowledge and skills for educators and cooks, findings from these studies suggest that improving knowledge and skills may not necessarily translate to improvements in children's dietary intake in the short term. Nonetheless, scalable interventions that increase educators' knowledge and skills in vegetable-related practices and/or teaching are valuable, and it is possible that continued intervention implementation and thus greater exposure for children to evidence-based practices (28) may lead to increases in children's usual vegetable intake. The pragmatic online self-delivered intervention approach, including real-world dissemination strategies used in the present study, was shown to be feasible and acceptable for adoption by Australian LDC centres and educators nationally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are limited studies investigating the impact of LDC interventions on TDF domains of knowledge and skills for educators and cooks, findings from these studies suggest that improving knowledge and skills may not necessarily translate to improvements in children's dietary intake in the short term. Nonetheless, scalable interventions that increase educators' knowledge and skills in vegetable-related practices and/or teaching are valuable, and it is possible that continued intervention implementation and thus greater exposure for children to evidence-based practices (28) may lead to increases in children's usual vegetable intake. The pragmatic online self-delivered intervention approach, including real-world dissemination strategies used in the present study, was shown to be feasible and acceptable for adoption by Australian LDC centres and educators nationally.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention consisted of two initiatives targeting the Mealtime environment and the Curriculum (19) , developed based on the Best Practice Guidelines for Increasing Children's Vegetable Intake in the Early Years (28) and draw on evidence for effective strategies for increasing vegetable intake and acceptance in the early years from a recent umbrella review (13) . The intervention was delivered online whereby at the beginning of the 12-week study period centre management were provided with a website link and instructions for accessing the initiatives via email.…”
Section: The Interventionmentioning
confidence: 99%
“…Three initiatives will be developed which draw on evidence for effective strategies for increasing vegetable intake and acceptance in the early years30 44 and align with best practice guidelines for increasing vegetable intake in LDC, which recommend multilevel and multicomponent interventions that combine strategies targeting children and the centre environment32 41 (table 1). The target audience of the initiatives will be children, educators and cooks.…”
Section: Methods and Analysismentioning
confidence: 99%
“…This study will be delivered and evaluated online, with all measures self-completed by participating centres using online data collection instruments. This approach will support centres to monitor their own progress towards increasing children’s vegetable intake, which will align the initiative package with Best Practice Guidelines 32 41. Data will be collected at baseline and 12 weeks.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation